Functional analysis of a novel mutation in the TIMM8A gene that causes deafness‐dystonia‐optic neuronopathy syndrome. Issue 3 (5th January 2020) - Neighbors, Addison; Moss, Tonya; Holloway, Lynda; Yu, Seok‐Ho; Annese, Fran; Skinner, Steve; Saneto, Russell; Steet, Richard
Abstract: Background: The rare, X‐linked neurodegenerative disorder, Mohr–Tranebjaerg syndrome (also called deafness‐dystonia‐optic neuronopathy [DDON] syndrome), is caused by mutations in the TIMM8A gene. DDON syndrome is characterized by dystonia, early‐onset deafness, and various other neurological manifestations. The TIMM8A gene product localizes to the intermembrane space in mitochondria where it functions in the import of nuclear‐encoded proteins into the mitochondrial inner membrane. Frameshifts or premature stops represent the majority of mutations in TIMM8A that cause DDON syndrome. However, missense mutations have also been reported that result in loss of the TIMM8A gene product. Methods: We report a novel TIMM8A variant in a patient with DDON syndrome that alters the initiation codon and employed functional analyses to determine the significance of the variant and its impact on mitochondrial morphology. Results: The novel base change in the TIMM8A gene (c.1A>T, p.Met1Leu) results in no detectable protein and a reduction in TIMM8A transcript abundance. We observed a commensurate decrease in the steady‐state level of the Tim13 protein (the binding partner of Tim8a) but no decrease in TIMM13 transcripts. Patient fibroblasts exhibited elongation and/or increased fusion of mitochondria, consistent with prior reports. Conclusion: This case expands the spectrum of mutations that cause DDON syndrome and demonstrates effects on mitochondrial morphology that are consistent with prior reports. Abstract : We report a novel TIMM8A variant in a patient with DDON syndrome that alters the initiation codon, resulting in no detectable protein and a reduction in TIMM8A transcript abundance. Decreased steady‐state level of the Tim13 protein and elongation and/or increased fusion of mitochondria were also observed in patient cells. This case expands the spectrum of mutations that cause DDON syndrome.